Classical Bianchi Type I Cosmology in K-Essence Theory - J. Socorro; Luis O. Pimentel; Abraham Espinoza-García (Advances in High Energy Physics)
We use one of the simplest forms of the K-essence theory and we apply it to the classical anisotropic Bianchi type I cosmological model, with a barotropic perfect fluid (p=γρ) modeling the usual matter content and with cosmological constant Λ. Classical exact solutions for any γ≠1 and Λ=0 are found in closed form, whereas solutions for Λ≠0 are found for particular values in the barotropic parameter. We present the possible isotropization of the cosmological model Bianchi I using the ratio between the anisotropic parameters and the volume of the universe. We also include a qualitative analysis of the analog of the Friedmann equation.